The relationship between self-esteem and learning reading and writing in sixth graders in the Hashemite Kingdom of Jordan) العلاقة بين تقدير الذات وتعلم القراءة والكتابة لدى طلاب الصف السادس الإبتدائي في المملكة الأردني ة الهاشمية - Farid Turki Jdeitawi,; Mohd. Aderi Che Noh,; Kamarulzaman Abdul Ghani, (Institut Kajian Rantau Asia Barat, 2012)
This study aims at investigating self-esteem relationship with learning reading and writing in sixth graders in public schools in the Hashemite kingdom of Jordan. This major goal includes the following items: identifying the level of self-esteem in sixth graders attending public schools at the Hashemite kingdom of Jordan, identifying their level of reading and writing, identifying the relationship between their level of self-esteem and their learning reading and writing. The population of the study includes all six-graders in public schools in Jordan, whereas multi-stages random sampling is used to choose the sample. This sample consists of 852 students, 460 males and 392 females. The following tools are used: Copper smith’s self-esteem questionnaire, reading and writing achievement test prepared by the researcher. The study has found out that the mean of self-esteem is average )3448(, the mean of learning reading and writing is above average )11492(.The study has also indicated a significant positive correlation between self-esteem and learning reading and writing )44154( which is statistically significant at (0.01). In light of these results, the researchers have recommended that self-esteem affects learners’ academic achievement. Therefore, teachers should improve their students’ self-esteem, encourage them, reinforce their positive behavior, and vary their educational activities to avoid routine and mechanical procedures. This helps students appreciate their efforts. Researchers have also recommended making programs for improving students’ self-esteem. Other recommendations include conducting more studies about self-esteem, learning reading and writing, and achievement in students belonging to different educational stages whether younger or older than those in this study.